Motif Mengunggah Video TikTok ke Dalam Media Sosial Instagram di Kalangan Remaja di Kota Denpasar - Mayreena Wibowo, Vinsensa Dianda; Purnawan, Ni Luh Ramaswati; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2021)
TikTok is a social media platform that supports its users to create and upload short videos easily and quickly. Although its reputation is better than Instagram in Top Apps Worldwide for July 2020 and has different typical users, many users have also uploaded TikTok videos on Instagram. The purpose of this research is to find out the motives of teenagers in Denpasar City to upload TikTok videos on Instagram. Data in this quantitative descriptive study were collected using a questionnaire and analyzed using descriptive statistic analysis techniques. Based on the uses and gratification theory as well as a combination of motives according to McQuail and Papacharissi and Rubin, the results show that the most encouraging motive for teenagers in Denpasar who upload TikTok videos on Instagram is pass time motive, while that is a less encouraging motive is social integration and interaction motive. Keywords: Motive, TikTok Video, Instagram, Teenager